The systematics and biology of Cotesia nonagriae (Olliff) stat. rev. (Hymenoptera: Braconidae: Microgastrinae), a newly recognized member of the Cotesia flavipes species complex - Muirhead, Kate; Austin, Andrew; Sallam, Mohamed (Zootaxa, 2008)
The Australian species Cotesia nonagriae Olliff stat. rev. (Hymenoptera: Braconidae) is redescribed and formally removed from synonymy with C. flavipes based on molecular, morphological and biological differences. The taxonomic history and phylogenetic relationships of C. nonagriae with other members of the C. flavipes complex are presented and underscore the importance of molecular-based identification within this group. The biology of C. nonagriae on the native noctuid stemborer host, Bathytricha truncata (Walker), is compared with previously recorded C. flavipes life history traits. The implications of this taxonomic study relative to biological control and importation of stemborer parasitoids into Australia are discussed.